2005
DOI: 10.1089/hum.2005.16.200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Intracellular Mobility and Nuclear Accumulation of DNA Plasmids Associated with a Karyophilic Protein

Abstract: The use of synthetic gene delivery systems in human gene transfer is hampered by poor transfection efficiencies, largely because of the inability of DNA to translocate across the nuclear pore complex. A means to overcome this barrier is to bind the DNA to nuclear localization signals (NLSs), which are recognized by shuttling receptors of the nuclear import machinery. Here, we studied the intracellular transport of plasmid DNA microinjected into HeLa cell cytoplasm, alone or as a complex with intact or NLS-dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 45 publications
2
85
0
Order By: Relevance
“…29,30 In addition, several groups have shown that by complexing plasmids with proteins, such as histone proteins and nuclear factor kB, or with peptide nucleic acids (PNAs) that contain nuclear localization signals, nuclear import and expression are enhanced. [31][32][33][34] As SRF and NK3 factors are coexpressed specifically in SMCs, other cell types are unable to form an import complex on the pDNA, making the SMGA promoter a tissuespecific DTS.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In addition, several groups have shown that by complexing plasmids with proteins, such as histone proteins and nuclear factor kB, or with peptide nucleic acids (PNAs) that contain nuclear localization signals, nuclear import and expression are enhanced. [31][32][33][34] As SRF and NK3 factors are coexpressed specifically in SMCs, other cell types are unable to form an import complex on the pDNA, making the SMGA promoter a tissuespecific DTS.…”
Section: Discussionmentioning
confidence: 99%
“…pDNA is however a large hydrophilic molecule which does not easily pass the hydrophobic central channel of the NPCs. Efforts to increase the nuclear import of pDNA through NPCs by the use of NLSs have met with limited success, although this strategy initially seemed very promising [163,164]. The use of…”
Section: Reflections On Therapeutic Strategies For the Improvement Ofmentioning
confidence: 99%
“…[111][112][113][114] Various synthetic and natural NLS, including viral coat proteins, increase transfection with non-viral vectors, whether or not they are covalently conjugated. 22,91,[115][116][117][118][119] Nuclear translocation is affected by several variables, including DNA conformation, the specific NLS, the number of NLS peptides conjugated to each DNA fragment, and the manner in which they are conjugated. In one study, transfection with linear DNA containing a NLS peptide failed to increase expression over plasmid DNA or linear DNA without an attached NLS.…”
Section: Nuclear Translocationmentioning
confidence: 99%